Efek Mulsa Tajuk Eceng Gondok (Eichhornia crassipes) Terhadap Fase Generatif Kacang Tunggak Nagara (Vigna unguiculata ssp. Cylindrica) - Danur Warisko Ageng Kurniawan; Tuti Heiriyani; Nurlaila Nurlaila; Hikma Ellya (Universitas Lambung Mangkurat, 2026)
Nagara cowpea (Vigna unguiculata ssp. cylindrica) is a legume with relatively high nutritional value, however, its cultivation is currently limited because it is less competitive than major legume crops such as mung bean and peanut. On the other hand, water hyacinth is a locally abundant resource with high organic matter content, yet it is often considered a weed due to its rapid growth. The objective of this study was to improve the productivity of Nagara cowpea by utilizing water hyacinth as organic mulch and to determine the effectiveness of shoot mulch of water hyacinth on the generative phase of Nagara cowpea. This study used a Completely Randomized Design (CRD) with a single-factor treatment consisting of three levels: no mulch as the control (m0), 4 kg fresh mulch (m1), and 4 kg dry mulch (m2), each replicated six times, resulting in 18 experimental units. The results showed that the application of water hyacinth mulch (Eichhornia crassipes) had no significant effect on any of the observed variables related to the generative phase of Nagara cowpea (Vigna unguiculata ssp. cylindrica).